(3GdYHGH aj GddZIs - (3GdMSf Hf eMeO Hf GdMSf Hf MjOQ GdYOhj GdYeQj GdUGZGfj GdMfaj QVqj GdOjf,J (B650 (3g` s
(3ChdgG (B:s
(3baRY GdbaYI TF THjg HGdRHjd HdG YQhI s
(3BNQgG (B:s
(3GdRZa ObGFb GdMWH hGdJQcjH jOd Ydi SYg haVd BNQ GdeLdO GdQGHY YTQ s
(3GdfSNI HgG MhGTs
(3LRC jHOC HeGOI baRYs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B232 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B279s
Keywords: (3GddZIs